Keruangan Perkotaan Medan dalam Tinjauan Transportasi Perkotaan Masa Kolonial - Syaiful Anwar (UIN Sumatera Utara Medan, 2017)
Abstract This research discusses the development of urban transport in Medan during the first half of 20th century. In this period, Medan was the city at outside Java that had the most good strides in social and economic life. Although the urban situation had a remarkable development, but the transport system was not complicated as well as Batavia or Surabaya. Therefore, the problem of this thesis emphasize the urban transportation development in the midst of Medan urban’s development. The urban spaces, the dynamics of employing transportation, and regulation are some important factors which discuss in this thesis. This research analyzing primary and secondary sources which include archives, newspapers, magazines, photographs, and other references. There are several findings in this thesis. First, most of the urban streets in Medan were built originally for the plantation needs, before then became the public road and the urban main street. Second, although the mechanic vehicle had existed, but generally, the urban center was filled by the smaller number of upper middle class rather than lower middle class groups which generally live at suburbs. Third, the policy on the Medan urban transport system was not fully held by the city government, because the other parties of non-government also intervenes to adjust their personal or group interests. Fourth, public transport which could carry mass passenger tends to be marginalized by economic reasons, i.e. the economic opportunity where people engaged in transportation was lost and effect on peoples income. Fifth, the sorts of urban transport in Medan are connoting also to social symbol.Keywords: Development, transportation, city, spatial.